Angiopoietin-like 8 Improves Insulin Resistance and Attenuates Adipose Tissue Inflammation in Diet-Induced Obese Mice - Luo, Deng; Chen, Xiaolin; Yang, Wenqiang; Ran, Wenzhuo; Wen, Zhongyuan (Experimental and Clinical Endocrinology & Diabetes, 2020)
Angiopoietin-like 8 (ANGPTL8) is closely linked to obesity-associated metabolic diseases and insulin resistance. The aim of the current study was to investigate the ability of ANGPTL8 to reverse insulin resistance in obese mice. The administration of ANGPTL8 reduced weight gain and improved glucose tolerance in mice with diet-induced obesity. In addition, ANGPTL8 administration modified macrophage infiltration, reduced monocyte chemoattractant protein-1 (MCP-1) and interleukin-1β(IL-1β) levels, and increased adiponectin gene expression in inguinal white adipose tissue (iWAT). Moreover, the exposure of a cultured peritoneal macrophage line to ANGPTL8 reduced the mRNA expression of M1 macrophage markers (TNF-α and IL-1β) upon stimulation with lipopolysaccharides in a dose-dependent manner. By contrast, when incubated with IL-4, exposure of macrophages to ANGPTL8 increased the mRNA expression of M2 macrophage markers (Arg1 and Chi3l3) in a dose-dependent manner. Collectively, the results of the present study demonstrated that treatment with ANGPTL8 can attenuate adipose tissue inflammation through regulation of macrophage polarization, and thus, it could be useful for improving insulin resistance.
Keywords: ANGPTL8; obesity-related inflammation; macrophage polarization; macrophage infiltration; insulin resistance